Marko Pohlin in Václav Rosa - Honzak-Jahić, Jasna (Slavistična revija, 2002)
Marko Pohlin's role model was, among other people, an artist of the Czech Baroque, the poet, grammarian, and lexicographer, Václav Jan Rosa. The purpose of this article is to show Rosa's (culture-formative, and, by extension, nation-formative) textual program and its causes. Since both Rosa and Pohlin were also creators of technical terminology, the uniting and distinctive features of it are presented as well.
Keywords: biografije; češčina; linguistics; lingvistika; Pohlin, Marko, 1735-1801; Rosa, Václav Jan, 1620-1689; Slovene; slovenščina; strokovna terminologija; vplivi; zgodovina jezika